Nexus of Gender Diversity and Corporate Governance: Ana-lyzing Their Effects on Firm Performance with Accrual Earning Management as a Moderating Factor - Mardianto Mardianto; Siti Eldiani Nurrahma (CV. Muris Global Education, 2026)
This study aims to examine the effect of board gender diversity, corporate governance quality, and accrual earnings management on firm performance. The research employs a quantitative approach using multiple regression analysis on secondary data obtained from the annual reports of companies listed on the Indonesian Stock Exchange. Firm performance is measured using return on assets (ROA), gender diversity is proxied by the proportion of female directors on the board, corporate governance quality is measured using the Corporate Governance Index (CGI), and accrual earnings management is measured using discretionary accruals based on the Jones Model. The results indicate that gender diversity has a positive and statistically significant effect on firm performance, suggesting that a higher presence of female directors is associated with better company performance. In contrast, corporate governance quality is found to have a negative and significant relationship with firm performance, indicating that higher governance scores do not necessarily translate into improved financial outcomes. Accrual earnings management also shows a positive and significant effect on firm performance, implying that higher discretionary accruals are associated with higher reported performance. This study contributes to the corporate governance literature by providing empirical evidence from an emerging market context and by highlighting the complex roles of gender diversity, governance quality, and earnings management in shaping firm performance.